The Urgency of Official Non-Halal Labels in Restaurants as a Consumer Protection in Indonesia - Putra, Yudha Pratama; Nurwahidin, Nurwahidin; Fatwa, Nur (Journal Of Middle East and Islamic Studies, 2024)
Information about non-halal labels is regulated by Law No. 33 of 2014 concerning Halal Product Guarantees. Article 93 states that products originating from prohibited materials must include non-halal details in the form of images, writing, or the name of the material with a different color in the composition of the material, for example red. In 2014, the Head of the Halal Registration and Certification Center at the BPJPH Ministry of Religion explained that his party would regulate the use of non-halal labels for non-halal products in the Minister of Religion regulations. However, until now, this plan has not been realized. official non-halal labels in restaurants in Indonesia as an effort to protect consumers. This research aims to design an official non-halal label to be applied in restaurants based on three categories: non-halal, halal in registration, and Halal be confirmed. The method used is descriptive qualitative and the label design method uses a Visual Communication Design approach which will be posted in restaurants and eateries. The research results are label concepts that will be applied in restaurants. By designing labels that are easy to see and read, this research seeks to increase the clarity of information and protect Muslim consumers.